Pengaruh Tambahan Penghasilan Pegawai (TPP) terhadap Kinerja Pegawai di Bagian Protokol dan Komunikasi Pimpinan Kota Batam - Erika, Tiara Devita; Alexsander, Alexsander; Aprianty, Henny (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Efforts to realize self-existence are something that is considered normal among women in early adulthood who will generally make various efforts to maintain or improve their physical condition in such a way as to get a positive assessment from their environment. This happens because the assessment of body image positively and negatively depends on the individual himself in perceiving himself about how he should behave according to personal standards. Self-concept and gratitude are related to how individuals perceive their body image to be positive. The purpose of this study was to empirically examine the relationship between self-concept and gratitude and body image in early adult women. The sample in this study were women aged 20-25 years in the Jakarta, Depok and Bekasi areas. Data collection using a questionnaire. This research method uses a quantitative design with multiple correlation data analysis techniques and Pearson product moment correlation analysis. The results of this study indicate that self-concept and gratitude simultaneously have a positive relationship with body image in early adult women by 67.7%. Partially, only gratitude has no relationship with body image.